Simultaneous administration of EZH2 and BET inhibitors inhibits proliferation and clonogenic ability of metastatic prostate cancer cells - Aide Negri; Marina Marozzi; Daniela Trisciuoglio; Dante Rotili; Antonello Mai; Federica Rizzi (Taylor & Francis Group, 2023)
Androgen deprivation therapy (ADT) is a common treatment for recurrent prostate cancer (PC). However, after a certain period of responsiveness, ADT resistance occurs virtually in all patients and the disease progresses to lethal metastatic castration-resistant prostate cancer (mCRPC). Aberrant expression and function of the epigenetic modifiers EZH2 and BET over activates c-myc, an oncogenic transcription factor critically contributing to mCRPC. In the present work, we tested, for the first time, the combination of an EZH2 inhibitor with a BET inhibitor in metastatic PC cells. The combination outperformed single drugs in inhibiting cell viability, cell proliferation and clonogenic ability, and concomitantly reduced both c-myc and NF-kB expression. Although these promising results will warrant further in vivo validation, they represent the first step to establishing the rationale that the proposed combination might be suitable for mCRPC treatment, by exploiting molecular targets different from androgen receptor.